Joule–Thomson expansion of higher dimensional nonlinearly AdS black hole with power Maxwell invariant source. (9th April 2021) - Feng, Zhong-Wen; Zhou, Xia; He, Guansheng; Zhou, Shi-Qi; Yang, Shu-Zheng
Abstract: In this paper, the Joule–Thomson expansion of the higher dimensional nonlinearly anti-de Sitter (AdS) black hole with power Maxwell invariant source is investigated. The results show the Joule–Thomson coefficient has a zero point and a divergent point, which coincide with the inversion temperature T i and the zero point of the Hawking temperature, respectively. The inversion temperature increases monotonously with inversion pressure. For the high-pressure region, the inversion temperature decreases with the dimensionality D and the nonlinearity parameter s, whereas it increases with the charge Q . However, T i for the low-pressure region increase with D and s, while it decreases with Q . The ratio η BH between the minimum inversion temperature and the critical temperature does not depend on Q, it recovers the higher dimensional Reissner–Nördstrom AdS black hole case when s = 1. However, for s > 1, it becomes smaller and smaller as D increases and approaches a constant when D → ∞ . Finally, we found that an increase of mass M and s, or reducing the charge Q and D can enhance the isenthalpic curve, and the effect of s on the isenthalpic curve is much greater than other parameters.